Single-molecule FRET studies in live bacteria - Plochowietz, A (2016)
Single-molecule fluorescence and single-molecule Förster resonance energy transfer (FRET) have proven enormously successful in understanding molecular and cellular processes over the last two decades. However, in vivo single-molecule FRET studies are still very difficult, mainly because they require site-specifically labelled biomolecules with photostable organic dyes. In this work, I established single-molecule FRET studies in live bacteria and applied the developed method to study mechanisms of gene expression and gene regulation. To begin with, I optimised a recently developed internalisation method based on electroporation for the efficient loading of bacterial cells with organic dye-labelled nucleic acids and proteins while maintaining cell viability. Following these studies, I internalised labelled tRNA molecules, measured their diffusion coefficient, and showed that most tRNA molecules diffuse freely in live bacteria. I also showed that bound tRNA molecules are predominantly at the cell periphery and compete with the endogenous tRNA pool during translation using antibiotic controls and simulations. Finally, I studied transcription initiation in vivo by internalising promoter DNAs with different FRET labelling schemes reporting on individual steps in transcription initiation. Thus, I observed single-molecule FRET signatures attributed to open complex formation, DNA scrunching during initial transcription, and promoter escape, which were not present in null-promoter DNA and antibiotic controls. By carefully designing single-molecule FRET assays, I imagine single-molecule FRET studies to become a major tool in understanding protein dynamics, and elucidating mechanistic details of gene regulation processes in living cells.